Electroconvulsive therapy for depression and oral dyskinesia in a patient who developed parkinsonism induced by valbenazine - Yuhei Mori; Yuhei Suzuki; Akiko Sato; Risa Shishido; Yuri Kobayashi; Yuta Fukuchi; Shota Inada; Yuka Iwasaki; Riko Sato; Keitaro Takada; Naoki Morita; Itaru Miura (PCN Reports, 2025)
Abstract Background Tardive dyskinesia (TD) is a movement disorder related to long‐term antipsychotic use and characterized by involuntary repetitive movements that often affect the oral and facial muscles. Although valbenazine, a vesicular monoamine transporter 2 (VMAT2) inhibitor, is an effective treatment of TD, it may induce drug‐induced parkinsonism (DIP) in some patients. Electroconvulsive therapy (ECT) improves depressive symptoms and certain movement disorders; however, its role in managing TD, particularly in patients intolerant to VMAT2 inhibitors because of DIP, remains elusive. Case Presentation Herein, we describe a 65‐year‐old Japanese woman with a history of major depressive episodes and oral dyskinesia. The patient was treated with valbenazine for oral dyskinesia; however, she developed DIP, requiring valbenazine discontinuation. After the worsening of depression, the patient was hospitalized and underwent 10 sessions of modified ECT, which remarkably helped improving depressive symptoms and oral dyskinesia. Conclusion This case suggests that ECT could be a viable treatment option for managing patients with depression and oral dyskinesia who are susceptible of valbenazine‐induced parkinsonism.